2012
DOI: 10.1105/tpc.111.094284
|View full text |Cite
|
Sign up to set email alerts
|

The Signal Transducer NPH3 Integrates the Phototropin1 Photosensor with PIN2-Based Polar Auxin Transport in Arabidopsis Root Phototropism

Abstract: Under blue light (BL) illumination, Arabidopsis thaliana roots grow away from the light source, showing a negative phototropic response. However, the mechanism of root phototropism is still unclear. Using a noninvasive microelectrode system, we showed that the BL sensor phototropin1 (phot1), the signal transducer NONPHOTOTROPIC HYPOCOTYL3 (NPH3), and the auxin efflux transporter PIN2 were essential for BL-induced auxin flux in the root apex transition zone. We also found that PIN2-green fluorescent protein (GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(168 citation statements)
references
References 64 publications
6
160
0
1
Order By: Relevance
“…The movement of the root away from light sources, or root negative phototropism, is dependent upon blue light perception by PHOTs (Wan et al, 2012). Contrary to the negative response to blue light, a positive growth response of the root to R light has also been observed , but this response is weak and can only be observed in the absence of gravity sensing Kiss et al, 2003).…”
Section: Light Affects Root Developmental Plasticitymentioning
confidence: 88%
See 3 more Smart Citations
“…The movement of the root away from light sources, or root negative phototropism, is dependent upon blue light perception by PHOTs (Wan et al, 2012). Contrary to the negative response to blue light, a positive growth response of the root to R light has also been observed , but this response is weak and can only be observed in the absence of gravity sensing Kiss et al, 2003).…”
Section: Light Affects Root Developmental Plasticitymentioning
confidence: 88%
“…There are two PHOTs identified in Arabidopsis, phot1 and phot2, with similar function and structure. Besides their function in the shoot, phot1 is also expressed in the roots, regulating root bending (Wan et al, 2012;Zhang et al, 2013). In contrast to other photoreceptors, which are present in the nucleus or cytoplasm, PHOTs are located in the plasma membrane (Sakamoto and Briggs, 2002).…”
Section: Photsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the polar targeting of a subset of PIN proteins (e.g., PIN1 and PIN2) is regulated by various protein trafficking pathways, including ADP ribosylation factor GTP-exchanging factor-dependent clathrinmediated internalization, Rab GTPases, and retromer complexmediated endosomal pathways (Geldner et al, 2001;Jaillais et al, 2006Jaillais et al, , 2007Michniewicz et al, 2007;Kleine-Vehn et al, 2008). The dynamic trafficking process that contributes toward facilitating the polar targeting of the newly synthesized nonpolar PINs to the plasma membrane (Dhonukshe et al, 2008) can be modified following physiological or environmental changes, resulting in the formation of altered intracellular auxin gradient as well as redirection of auxin flow (Paciorek et al, 2005;Laxmi et al, 2008;Shibasaki et al, 2009;Wan et al, 2012). These observations raise an interesting possibility that auxin homeostasis under high temperature may be modulated by intracellular protein trafficking pathways.…”
Section: Introductionmentioning
confidence: 99%